The presocratic philosophical legacy of ancient Greece and its influence on Zoroastrian eschatology - Sayyed Toufiq Hosseini (تاریخ نگری و تاریخ نگاری, 2022)
The Gathas, as Zoroaster's own compositions, contain the oldest eschatological material, describing a picture of the future with a clear vision of the victory of right over wrong. The revelatory character of the text is about an involuntary and inevitable future, but in the text of the Gathas Zarathustra speaks of free will and discretion in this victory. In fact, Zarathustra conception of this victory is based on a moral progress that leads to a voluntary decision for what is right. After the Gathas and also brief portions of the young Avesta, the most detailed accounts of the eschatology of this religion are found in the Pahlavi texts. The remarkable point is that the revelations narrated in these texts describe a dark future and the destruction of humanity in a picture completely opposed to the thoughts of Zarathustra. Undoubtedly, this contradiction in the description of the afterlife in the Zoroastrian religion shows the evolution in the intellectual n ature and the structure of the philosophy of the history of the Zoroastrian religion, which has occurred under the influence of the political and social transformations of the Zoroastrian world and its confrontation with other ideas and religions. Based on this, the main problem of this research is to investigate the evolution of Zoroastrian religion's revelatory ideas, and especially the origin of the world's ages and metals in the later texts of Zoroastrian religion. By examining the texts and sources of Zoroastrian religion and Greek and Roman texts, this research concludes that with the political transformations and the collapse of the Achaemenid government and the domination of the Macedonian government over Zoroastrian land, the revelatory works of Zoroastrian religion were changed and transformed to explain and justify the situation. Based on Stoic-Hellenic revelatory texts, which presented a deteriorating image of the end of mankind, these narratives made the chaotic state of the Zoroastrian society after the fall of the Achaemenids acceptable and rational.